Peningkatan Hasil Belajar Tematik Terpadu Dengan Model Kooperatif Tipe STAD di Kelas V SDN 11 Lubuk Batuang, Kab.Solok Selatan - Fauziah, Siti Rahmah; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
The aim of this research is to describe the improvement in student learning outcomes in integrated thematic learning with a cooperative type model Student Team Achievement Division (STAD) in class V at SDN 11 Lubuk Batuang. This type of research is classroom action research using qualitative and quantitative approaches. This research was carried out in the second semester of the 2021/2022 academic year. The research subjects were 32 fifth-grade students, the researcher played the role of practitioner, the class teacher played the role of observer. The research was carried out in II cycles: cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. The research results showed that the increase in RPP cycle I obtained an average score of 79.16% with qualifications (C), increasing in cycle II to 94.44% with qualifications (SB). The average value of the first cycle teacher aspect was obtained at 80.35% with qualification (B), increasing in cycle II to 96.42% with qualification (SB). Meanwhile, the average value for aspects of the first cycle students obtained was 80.35% with a qualification (B), increasing in the second cycle to 96.42% with a qualification (SB). Student learning outcomes in cycle I obtained an average score of 70.91 and increased in cycle II with an average score of 87.30. It can be concluded that by using the Cooperative Type model Student Team Achievement Division can improve student learning outcomes in integrated thematic learning in Class V SDN 11 Lubuk Batuang.